Congressional Hearing on Near‐Earth Objects Brings Reassurances and "What If" Questions. (2nd April 2013) - Showstack, Randy
Abstract : Despite repeated reassurances from Obama administration officials that it is unlikely that a near‐Earth object (NEO) could cause catastrophic damage on Earth anytime over the next several hundred years, members of the U.S. House of Representatives Committee on Science, Space, and Technology kept raising "what if" questions at a 19 March hearing about threats from space.